2006
DOI: 10.1017/s0022215106004944
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic adequacy and accuracy of fine needle aspiration cytology in neck lump assessment: results from a regional cancer network over a one year period

Abstract: This audit demonstrated widespread diagnostic difficulties associated with head and neck FNAC in a large patient sample. It is likely that these problems will be mirrored in other cancer networks. In order for one-stop head and neck clinics to succeed, the non-diagnostic rate of FNAC in particular must be minimised. There are strategies to enable this, depending on local resources, including increased access to cytologists or cytology technicians, diagnostic ultrasound, image guidance for FNAC and the use of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 12 publications
7
91
2
4
Order By: Relevance
“…Howlett, D.C., et al, studied a total of 276 patients and found FNAC of neck nodes to have a sensitivity of 89% and a specificity of 57%; for thyroid masses, the sensitivity was 62% and specificity was 86%; and for salivary glands, the sensitivity was 64% and specificity was 100%. 8 Tilak, V., Dhaded, A.V., et al, studied 550 patients and found the overall sensitivity of FNAC for neck masses to be 90.91% and specificity to be 93.18% which is greater than that observed in our study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Howlett, D.C., et al, studied a total of 276 patients and found FNAC of neck nodes to have a sensitivity of 89% and a specificity of 57%; for thyroid masses, the sensitivity was 62% and specificity was 86%; and for salivary glands, the sensitivity was 64% and specificity was 100%. 8 Tilak, V., Dhaded, A.V., et al, studied 550 patients and found the overall sensitivity of FNAC for neck masses to be 90.91% and specificity to be 93.18% which is greater than that observed in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…7 FNAC is particularly helpful in the workup of cervical masses and nodules because biopsy of cervical lymphadenopathy should be avoided until all diagnostic modalities have failed to establish diagnosis. 8 FNAC is clearly no substitute for histology, especially in determination of nodal architecture in lymphoma, the malignant pattern of follicular thyroid tumor, intracapsular spread in squamous carcinoma or in the distinction of pleomorphic from monomorphic adenoma. 4 The purpose of this study was to evaluate the adequacy and accuracy of FNAC in diagnosis of neck mass.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinicians and pathologists appreciate the benefits and limitations of cytological diagnosis and are likely familiar with reports of FNAC-histology correlation studies in the head and neck region which highlight the importance of cytopathologist experience and expertise and that the diagnostic accuracy is dependent on the site of aspiration with particular difficulties in differentiating reactive lymphoid hyperplasia from lymphoma and in diagnosing follicular thyroid lesions [31][32][33]. A recent study of 191 salivary gland FNACs from a single academic center [34] reported 79.1% overall accuracy in distinguishing benign from malignant lesions and the sensitivity for salivary neoplasia was 89.4%.…”
Section: Categorization Of Diagnostic Discrepanciesmentioning
confidence: 99%
“…Thus, FNAC is considered as an ideal method for diagnosing the nature of lesions. [5,6] The diagnosis of metastatic tumor to the lymph node by cytomorphological pattern is highly reliable and it is a sole indicative procedure for evaluating primary tumor in case of the occult primary. [7,8,9] In case of non-neoplastic lesions, the varied morphological patterns can mimic the other reactive conditions and it can lead to multiple differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%